Proliferative arrest and rapid turnover of thymic epithelial cells expressing Aire - Gray, Daniel (The Rockefeller University Press, 2007)
Expression of autoimmune regulator (Aire) by thymic medullary epithelial cells (MECs) is critical for central tolerance of self. To explore the mechanism by which such a rare cell population imposes tolerance on the large repertoire of differentiating thymocytes, we examined the proliferation and turnover of Aire(+) and Aire(−) MEC subsets through flow cytometric analysis of 5-bromo-2′deoxyuridine (BrdU) incorporation. The Aire(+) MEC subset was almost entirely postmitotic and derived from cycling Aire(−) precursors. Experiments using reaggregate thymic organ cultures revealed the presence of such precursors among Aire(−) MECs expressing low levels of major histocompatibility complex class II and CD80. The kinetics of BrdU decay showed the Aire(+) population to have a high turnover. Aire did not have a direct impact on the division of MECs in vitro or in vivo but, rather, induced their apoptosis. We argue that these properties strongly favor a “terminal differentiation” model for Aire function in MECs, placing strict temporal limits on the operation of any individual Aire(+) MEC in central tolerance induction. We further speculate that the speedy apoptosis of Aire-expressing MECs may be a mechanism to promote cross-presentation of the array of peripheral-tissue antigens they produce.